2015
DOI: 10.1109/tcpmt.2015.2424071
|View full text |Cite
|
Sign up to set email alerts
|

A Laser-Assisted Bonding Method Using a Liquid Crystal Polymer Film for MEMS and Sensor Packaging

Abstract: In this paper, we present the development of a laser-based bonding method using a liquid crystal polymer (LCP) film for cavity-based packaging of sensors and Microelectromechanical systems (MEMS) devices. LCP films possess the best properties among polymeric materials in terms of moisture resistance and temperature stability. We show that high-quality bonding of silicon and glass substrates as well as encapsulation of molded LCP packages can be obtained using a laser-assisted bonding method. Shear and leak tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The loss measurement and mechanical measurement show that the influence of LCP packaging on the performance of the phase shifter can be ignored, but it can maintain the equipment’s flexibility and protect it against various environmental conditions. LCPs are not only used in flexible RF MEMS, but also widely used in various flexible conformal RF devices and in various flexible MEMS sensors [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ].…”
Section: Materials For Flexible Rf Memsmentioning
confidence: 99%
“…The loss measurement and mechanical measurement show that the influence of LCP packaging on the performance of the phase shifter can be ignored, but it can maintain the equipment’s flexibility and protect it against various environmental conditions. LCPs are not only used in flexible RF MEMS, but also widely used in various flexible conformal RF devices and in various flexible MEMS sensors [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ].…”
Section: Materials For Flexible Rf Memsmentioning
confidence: 99%
“…The package performance measured up to standard, evaluated via shear test and reliability tests. Jiang et al [ 8 ] used a laser-assisted bonding method for a cavity-based package with a liquid crystal polymer (LCP). Their results showed that both silicon and glass substrates had high bonding quality.…”
Section: Introductionmentioning
confidence: 99%